Insular iconographies essays in honour of Jane Hawkes - Hawkes, Jane; Boulton, Meg; Bintley, Michael D. J. (Boydell studies in medieval art and architecture, 2019)
Professor Jane Hawkes has devoted her career to the study of medieval stone, exploring its iconographies, symbolic significances and scholarly contexts, and shedding light on the obscure and understudied sculpted stone monuments of Anglo-Saxon England. This volume builds on her scholarly interests, offering new engagements with medieval culture and the current scholarly methodologies that shape the discipline. The contributors approach several significant objects and texts from the early and later Middle Ages, working across several disciplinary backgrounds and periods, largely focusing on the Insular World as it intersects with wider global contexts of the period. The chapters cover a wide range of subjects, from the material culture of baptism, to the material, symbolic and iconographic consideration of the artistic outputs of the Insular world, with essays on sculpture, metalwork, glass and manuscripts, to ideas of stone and salvation in both material and textual contexts, to intellectual puzzles and patterns - both material and mathematic - to consideration of the ways in which the conversion to Christianity played out on the landscape